COCREATE: a self-directed learning approach to agricultural extension programmes. Issue 5 (4th July 2021) - Kusnandar, K.; van Kooten, O.; Brazier, F. M.
ABSTRACT: Participation has been proposed to improve agricultural extension programmes in developing countries. This paper reports on experience with COCREATE, an approach to agricultural extension programmes that supports agricultural chain actors in self-directed learning in action research with smallholder farmers and local traders in Indonesia. This approach resulted in the changes in relation and task division between farmers and their local traders in the agricultural production and supply and chains, improved their market position and in new institutions.